دور الثقافة التنظيمية الأخلاقية في تحقيق الالتزام التنظيمي لدى العاملين في جامعة بنغازي الليبية - القاز، نورا عبدالقادر محمود (جامعة قناة السويس - كلية التجارة بالاسماعيلية, 2019)
هدفت الدراسة للتعرف على دور الثقافة التنظيمية الأخلاقية في تحقيق الالتزام التنظيمي لدى العاملين في جامعة بنغازي الليبية، وتم استخدام المنهج التحليلي الوصفي، ولقد تم تصميم أداة القياس هي الاستبيان وتم توزيعهما على عينة عشوائية طبقية من العاملين لدي جامعة بنغازي، وتم استخدام برنامج التحليل الإحصائي SPSS لاختبار فرض الدراسة، وتوصلت الدراسة إلي وجود أثر إيجابي للثقافة التنظيمية الأخلاقية في تحقيق الالتزام التنظيمي لدى العاملين في جامعة بنغازي الليبية، وأوصت الدراسة بضرورة زيادة الاهتمام بالثقافة التنظيمية الأخلاقية لما لها من أثر إيجابي في تحقيق الالتزام التنظيمي لدى العاملين في جامعة بنغازي الليبية.
The study aimed to identify the role of ethical organizational culture in achieving the organizational commitment of the staff at Benghazi University of Libya, The descriptive analytical method was used. The measurement tool was designed and distributed to a stratified random sample of Benghazi University employees. The study concluded that there is a positive effect of the ethical organizational culture in achieving the organizational commitment of the employees of Benghazi University of Libya. The study recommended the need to increase attention to the ethical organizational culture because of its positive effect in Coordination of organizational commitment among workers in Benghazi, the Libyan University.
Keywords: الثقافة التنظيمية -- القيم الأخلاقية -- الإلتزام التنظيمى -- جامعة بنغازى -- ليبيا